Sistem Monitoring Ruangan berbasis Raspberry Pi dan Motion - Deddy Prayama -; Arya Aulia - (Jurnal Ilmiah Poli Rekayasa, 2015)
Lately, room security is a problem faced by many agencies end. It has become a vital necessity if the room equipped with many resources or has a limited access only to specific users only. Closed Circuit Television is one of the solutions to be able to record events that occur in a room that is monitored, but it is becoming redundant if everything is recorded. This system combines the use of a web camera and its peripheral devices to be able to record the events in a room if the detected movement. This system is more efficiently use space on the hard drive so that only record events in case of movement or change in a room..This system is accessible from the web.